PELATIHAN ANALISIS KEBUTUHAN UNTUK PENGEMBANGAN PROGRAM DI LEMBAGA KESEJAHTERAAN SOSIAL DAERAH ISTIMEWA YOGYAKARTA - Wijayanto, Arif; Hiryanto; Lutfi Wibawa; Serafin Wisni Septiarti; Neng Desi Aryani5; Puji Yanti Fauziah (Universitas PGRI Yogyakarta, 2025)
The needs analysis training is expected to improve the competency of Lembaga Kesejahteraan Sosial (LKS) Daerah Istimewa Yogyakarta, both in terms of conceptual understanding and practical skills. Through appropriate training, participants will be trained to collect, analyze, and interpret community needs data accurately. Community service through training programs is an effective way to make a direct contribution to the community. This activity was designed in conjunction with the coordination of the LKS/LKSA Forkom Bantul district, attended by all LKS managers/administrators throughout the Bantul district, 32 institutions, and representatives from the Bantul Regency Social Service. This training activity was carried out through several stages: Preparation, program socialization, program implementation, and evaluation. The training on needs analysis for program development at LKS has succeeded in providing participants with a deep understanding of the importance of needs analysis in designing effective and responsive programs. Keywords: Training, needs analysis, Lembaga Kesejahteraan Sosial